Resisting silence: moments of empowerment in Iranian women's blogs. (22nd December 2016) - Jaborooty, Maryam; Baker, Paul
Abstract : This paper illustrates how women in Iran use blogs to write about their relationships and feelings as a way of providing momentarily empowerment in a society that places restrictions on their freedom. We examine a relatively under-explored form of blogging, common to Iran, which we call 'love blogging', and we carry out a qualitative analysis of a small sample of four blog postings from different Iranian women which are used to illustrative different techniques that women use in order to challenge hegemonic gendered discourses in their society. We show how Iranian women use blogs as a way of revealing their innermost thoughts, creating alternative identities and articulating what is left 'unsaid' to their partners. The postings chosen highlight the disempowered status of women in Iranian society, from staying at home to carry out servicework to cases of marital rape and other forms of violence which Iranian women are expected to silently endure. The blog postings also indicate how women use techniques to avoid censorship, including use of metaphor, ambiguity, altered idioms and images.